JURIDICAL ASPECTS OF THE AGREEMENT FOR RESULTS: A STUDY OF LAW NO. 2 OF 1960 CONCERNING RESULTS - H.Nurdin (P3M Stia Al Gazali Barru and Meraja media, 2019)
[Full Paper] to pdf Copyright (c) 2019 Meraja journal